Systematic Review and Bioliometric Analysis of Genetic Factors Influencing Hematologic Traits: Implications for Blood Donor Screening - Aishah Farliani Shirat; Mohd Zaki Salleh; Nurul Aqmar Mohamad Nor Hazalin; Mohd Salleh Rofiee; Mohammad Masrin Md Zahrin; Thane Moze Darumalinggam; Nurul Azmir Amir Hashim; Adzrool Idzwan Ismail; Teh Lay Kek (Journal of Clinical and Health Sciences, 2026)
Introduction: Understanding the genetic influences on blood disorders related to iron metabolism, hemoglobin levels, and thrombophilia in diverse blood donor populations is essential for ensuring donor safety and maintaining a high-quality blood supply. This review explores the genetic factors contributing to these disorders and their impact on blood donors, with the aim of improving donor screening, optimizing blood donation practices, and enhancing transfusion safety. Method: MeSH keywords linked to single nucleotide polymorphisms (SNPs) were used to search the PubMed, Web of Science, and Scopus databases. Articles published between 2000 and September 2023 were included in this search. Only articles on human subject and written in English language were included in this review. Results: 1,292 articles were screened, twenty were selected for methodological quality assessment using the NOS scale, with scores ranging from 6 to 9. The studies extracted from databases were subjected to an analysis of terms of bibliographic coupling for the articles, co-authorship of authors and co-occurrence of keywords using the VOSviewer algorithm for the construction of bibliometric maps. This systematic review revealed gene polymorphisms and mutations in genes associated with blood disorders and the diseases mechanisms. SNPs suitable for screening blood donors have been identified, allowing for the detection of individuals who may be prone to iron deficiency, hemochromatosis, or other related conditions. Conclusion: Considering genetic factors is essential for understanding variations in blood composition across different populations. This knowledge enhances diagnosis, treatment, transfusion safety, and clinical practices, leading to better outcomes in blood recipients. Furthermore, this review provides insights into SNPs which had been reported to be associated with blood disorders and genetic panels can be developed to investigate their presence in the local populations.